2017
DOI: 10.1016/j.bone.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs 223-3p and 93-5p in patients with chronic kidney disease before and after renal transplantation

Abstract: Chronic kidney disease (CKD) is associated with a multifactorial dysregulation of bone and vascular calcification and closely linked to increased cardiovascular mortality and concomitant bone disease. We aimed to investigate specific microRNA (miRNA) signatures in CKD patients to find indicators for vascular calcification and/or bone mineralization changes during CKD and after kidney transplantation (KT). A miRNA array was used to investigate serum miRNA profiles in CKD patients, then selected miRNAs were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 65 publications
(82 reference statements)
2
51
0
Order By: Relevance
“…This is a common complication in CKD that affects the vascular system due to pathological deposition of calcium and phosphate in the vessels (Metzinger-Le Meuth et al, 2017). Also, Ulbing et al (2017) have shown that the expression of seric miR-223 is decreased in a murine model of CKD; decreased levels of seric miR-223 are also used to confirm CKD stage 4 and 5 diagnosis in patients with CKD. In this context, the levels of miR-155, miR-125b, and miR-145 are also decreased in stage 3-5D CKD patients .…”
Section: Vsmcs Contractility and Proliferationmentioning
confidence: 99%
“…This is a common complication in CKD that affects the vascular system due to pathological deposition of calcium and phosphate in the vessels (Metzinger-Le Meuth et al, 2017). Also, Ulbing et al (2017) have shown that the expression of seric miR-223 is decreased in a murine model of CKD; decreased levels of seric miR-223 are also used to confirm CKD stage 4 and 5 diagnosis in patients with CKD. In this context, the levels of miR-155, miR-125b, and miR-145 are also decreased in stage 3-5D CKD patients .…”
Section: Vsmcs Contractility and Proliferationmentioning
confidence: 99%
“…Various microRNAs have been implicated in DN pathogenesis (20), and the signature of circulating miRNAs can be used to predict disease progression (21). MiR-93 regulates microvascularization in the kidney and reduces angiogenesis by downregulating vascular endothelial growth factor (VEGF) (22,23). The aim of this study was to determine the expression levels of serum miR-93 in diabetic patients with and without nephropathy and compare that to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, downstream miRNAs derived from miR‐142 (miR‐142‐5p and miR‐142‐3p) are associated with AR, chronic rejection, and/or fibrosis across all four major solid organ transplantations . Levels of miR‐223p‐3p and miR‐93‐5p were shown to be present in CKD stages , which may also have broad utility for routine monitoring of kidney function in cardiac and other allograft patients especially when combined with miRNAs that are known to have clinical utility in post‐transplant surveillance. Furthermore, assessment of 10 genes expressed in blood that are diagnostic of kidney acute rejection was shown to have utility in a study of 250 blood samples from heart transplant recipients with and without acute rejection, indicating common pathways of immune activation .…”
Section: Discussion and Future Directionsmentioning
confidence: 99%